Copper‐Catalyzed Cross‐Coupling of Boronic Esters with Aryl Iodides and Application to the Carboboration of Alkynes and Allenes1. (14th February 2014) - Zhou, Yiqing; You, Wei; Smith, Kevin B.; Brown, M. Kevin
Abstract Copper‐catalyzed Suzuki–Miyaura‐type cross‐coupling and carboboration processes are reported. The cross‐couplings function well with a variety of substituted aryl iodides and aryl boronic esters and allows for orthogonal reactivity compared to palladium‐catalyzed processes. The carboboration method includes both alkynes and allenes and provides access to highly substituted and stereodefined vinyl boronic esters. The alkyne carboboration method is highlighted in the simple one‐pot synthesis of Tamoxifen.